2020
DOI: 10.3390/min10050440
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Elements in Iron-Manganese Formations in Bottom Sediments of Lake Onego (NW Russia) and Small Lakes (Shotozero and Surgubskoe) of Adjacent Territories

Abstract: The morphology and mineralogical and geochemical compositions of the freshwater ferromanganese formations (FMF) of Lake Onego (NW Russia) and small lakes located in its catchment area were studied. The lake waters, bottom sediments and FMF were analyzed by a set of modern methods of geochemistry, mineralogy, and crystal chemistry (powder X-ray diffraction, IR spectroscopy, electron microscopy, ICP–MS analysis, atomic absorption, etc.). A detailed description of the microscopic structure in comparison with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In addition to these minerals, there are opal (diatoms), Fe-Illite, and Fe-chlorite. [21]. The concentration of rhodochrosite, siderite, and vivianite increases in the zones of gas-saturated Silts (Figure 16).…”
Section: Mineralogy In Cores Ong-4 and Ong-7mentioning
confidence: 96%
See 1 more Smart Citation
“…In addition to these minerals, there are opal (diatoms), Fe-Illite, and Fe-chlorite. [21]. The concentration of rhodochrosite, siderite, and vivianite increases in the zones of gas-saturated Silts (Figure 16).…”
Section: Mineralogy In Cores Ong-4 and Ong-7mentioning
confidence: 96%
“…According to previous studies conducted by the authors, it was found that the mineral composition of the bottom sediments of lake Onega is formed by minerals (quartz, feldspar, muscovite), which were introduced into the lake from river runoff and aerosols, as well as autigenic minerals. In contrast to wells from other areas of the lake, the mineral phases of Fe and Mn are represented by pyrolusite, vivianite, rhodochrosite, and siderite already in the upper first centimeters of sediments [17,21]. In addition to these minerals, there are opal (diatoms), Fe-Illite, and Fe-chlorite.…”
Section: Mineralogy In Cores Ong-4 and Ong-7mentioning
confidence: 97%
“…However, since minor changes in the Eh and pH of the medium lead to great changes in sedimentary Mn/Fe ratios [53], the rims of Mn in the siderite might indicate subtle varying water conditions during the crystal growth, which is different from the modern ferruginous lakes [21].…”
Section: Weakly Alkaline and Manganese-ferruginous Pore Watermentioning
confidence: 99%
“…The geochemical and mineral compositions of the Lake Onego bottom sediments are described in detail in [31][32][33] The authors suggest that the upper part (0-20 cm) of the Holocene bottom sediments can be divided into two stratigraphic types, based on the mineralogical composition and geochemical features. The first type of bottom sediments is characterized by the presence of enriched Fe-Mn layers formed near the water-bottom sediment boundary.…”
Section: Mercury In the Bottom Sedimentsmentioning
confidence: 99%